The Evaluation of Dark Chocolate-Elicited Emotions and Their Relation with Physico Chemical Attributes of Chocolate - Elena Bartkiene (Foods, 2021)
The aim of this study was to evaluate the effect of different origin (Venezuela, Ghana, Peru) dark chocolates on emotions induced for consumers, and to analyse the relationships among overall acceptability (OA), emotions, and physicochemical attributes of the chocolate (fatty acids (FAs) and volatile compounds (VC)). Chocolate-elicited emotions were measured with FaceReader 8 software, scaling 10 emotion patterns (neutral, happy, sad, angry, surprised, scared, disgusted, contempt, valence, arousal). The OA was carried out by using a 10-point hedonic scale, ranging from 1 (extremely dislike) to 10 (extremely like). The obtained results showed that, among all chocolate-elicited emotions, the intensity of “happy” was the highest. In most cases, the influence of the different origin chocolate on the emotions induced for consumers was significant (except on emotions “neutral”, “scared”, and “disgusted”). Significant differences between the tested chocolates OA were not found. The origin of chocolate had a significant effect on most of the identified VC and the content of the main FAs (methyl palmitate, methyl stearate, cis,trans-9- oleic acid methyl ester, and methyl linoleate). Significant correlations between chocolate-elicited emotions and separate FAs and VC were found. Finally, this study showed that the origin of dark chocolate significantly influenced most of chocolate-elicited emotions and physicochemical attributes of chocolate, while separate FAs or VC can be used as chocolate quality indicators related to the chocolate OA, as well as chocolate-elicited emotions.